Serial changes in patient-reported outcome measures and satisfaction rate during long-term follow-up after total knee arthroplasty: a systematic review and meta-analysis - Jisu Park; Moon Jong Chang; Tae Woo Kim; Darryl D. D’Lima; Hyunkwon Kim; Hyuk-Soo Han (Knee Surgery & Related Research)
Abstract Purpose This study aimed to investigate the sequential changes in patient-reported outcome measures (PROMs) and the satisfaction rate during long-term follow-up after total knee arthroplasty (TKA). Methods Studies published until December 2023 were searched in MEDLINE, EMBASE, SCOPUS and Cochrane Library. The inclusion criteria were TKA as the primary procedure, a final post-operative follow-up period of at least seven years and reporting of PROMs data. The exclusion criteria were studies not reporting serial data of the same patient cohort, studies without mid-term data, comparative studies and reviews, comments or practice guidelines. Heterogeneity was assessed with the I 2 and tau 2 statistics. The quality of each study was evaluated using the methodological index for non-randomized studies (MINORS) criteria. The follow-up periods were divided into short-term, mid-term and long-term. Data were synthesised by narrative reviews and random-effects meta-analysis using standardised mean difference. Results Among the 13 studies included in the review, six were included in the meta-analysis. The overall PROMs were maintained until the mid-term (0.14; 95% CI [confidence interval], −0.05 to 0.34; I 2 = 96%; tau 2 = 0.10; P = 0.16), but declined in the long-term (−0.23; 95% CI −0.34 to −0.13; I 2 = 88%; tau 2 = 0.04; P < 0.0001). According to the subgroup analysis, pain improved from the short-term to mid-term (0.21; 95% CI 0.14 to 0.29; I 2 = 0%; tau 2 = 0). Subscales including function (−0.28; 95% CI −0.52 to −0.03; I 2 = 94%; tau 2 = 0.09) and objective measure (−0.23; 95% CI −0.31 to −0.15; I 2 = 62%; tau 2 = 0.01) declined from the mid-term to long-term. The patient satisfaction rate remained consistent throughout the study period. Conclusions The overall PROMs after TKA were maintained, with improvement observed in the pain subscale until the mid-term follow-up. However, in the long-term, overall PROMs, including function and objective measure, declined compared with those in the mid-term. Despite the decline in the physical aspects of PROMs over the long-term follow-up period, the patient satisfaction rate remained consistently high throughout the study period. Providing this information to patient pre-operatively may assist in establishing realistic expectations. Trial Registration This research was registered at PROSPERO (registration number: CRD42024578579).